Pengembangan Sistem Pembelajaran Berbasis Blended Learning Untuk Menunjang Merdeka Belajar di Lingkungan Internal SMKN 1 Balikpapan - Ihsan Ihsan; Nur Yanti; Dwi Lesmideyarti (Universitas Negeri Gorontalo, 2023)
This activity was carried out with a background of wanting to implement relevant knowledge to help problems that exist in society, especially in the field of information technology. Such as Blended Learning combines offline class instructions with online (computer) instruction with the hope that students will be able to solve problems related to learning content independently or in groups, according to the abilities of each student. This activity was carried out using the waterfall method approach with the creation of a learning, training, discussion and evaluation system. The method for creating a learning system is using Moodle and the MySQL database which will be installed on the internal server of SMK Negeri 1 Balikpapan. This activity produces a Blended Learning system that can be easily used by teachers and students to support Independent Learning and can increase the interest and quality of student learning at SMKN 1 Balikpapan.